Metabolic correlates to critical speed in murine models of sickle cell disease - Cendali, Francesca I.; Nemkov, Travis; Lisk, Christina; Lacroix, Ian S.; Nouraie, Seyed-Mehdi; Zhang, Yingze; Gordeuk, Victor R.; Buehler, Paul W.; Irwin, David; D’Alessandro, Angelo (Frontiers in Physiology, 2023)
Exercise intolerance is a common clinical manifestation in patients with sickle cell disease (SCD), though the mechanisms are incompletely understood. Here we leverage a murine mouse model of SCD, the Berkeley mouse, to characterize response to exercise via determination of critical speed (CS), a functional measurement of mouse running speed upon exerting to exhaustion. Upon observing a wide distribution in CS phenotypes, we systematically determined metabolic aberrations in plasma and organs – including heart, kidney, liver, lung, and spleen - from mice ranked based on CS performances (top vs bottom 25%). Results indicated clear signatures of systemic and organ-specific alterations in carboxylic acids, sphingosine 1-phosphate and acylcarnitine metabolism. Metabolites in these pathways showed significant correlations with CS across all matrices. Findings from murine models were thus further validated in 433 SCD patients (SS genotype). Metabolomics analyses of plasma from 281 subjects in this cohort (with HbA<10% to decrease confounding effects of recent transfusion events) were used to identify metabolic correlates to sub-maximal exercise test performances, as measure by 6 minute walking test in this clinical cohort. Results confirmed strong correlation between test performances and dysregulated levels of circulating carboxylic acids (especially succinate) and sphingosine 1-phosphate.